Role of turmeric in management of alveolar osteitis (dry socket): A randomised clinical study - Parveen Akhter Lone; Syed wakeel Ahmed; Vivek Prasad; Bashir Ahmed (Elsevier, 2018)
Plants & their extracts have immense potential for the management or treatment of the wounds. The pyhto medicines for the wound healing are not only cheap & affordable but are purportedly safe as hypersensitivity reactions are rarely encountered with the use of these agents, these natural agents induce healing & regeneration of the lost tissue by multiple mechanisms Turmeric commonly is called as Haldi in Hindi. C Longa has been reported to possess anti bacterial, anti fungal & anti inflammatory activities. Turmeric is known as traditional herb to Asia & India also called as curcuma longa, with maximum healing properties & other great uses. It is widely used in India & China for traditional Chinese medicine. This act as anti inflammatory agent to treat different kind of diseases & health problems. Aims & objectives: The aim of this study was to study the therapeutic, healing benefits of turmeric, an herb commonly used in Asia Material & methods: The study was conducted in department of oral & maxillofacial surgery of Indira Gandhi government dental college jammu.178 patients were selected from the outpatient department of oral & maxillofacial surgery. The diagnosis of dry socket was made clinically. Turmeric dressing with mustard oil was given in group A & in group B ZOE dressing was given. Results: In this study there was significant reduction in pain, inflammation & discomfort after turmeric and ZOE dressing. Wound healing was seen faster, than dressing with ZOE. There is no side effect of Turmeric. Statistical analysis was done p < 0.05, was found statistically significant